Time management practice and associated factors among employees working in public health centers, Northwest Ethiopia: a mixed method study - Sisay Terefe; Lake Yazachew; Desale Bihonegn Asmamaw; Tadele Biresaw Belachew; Amsalu Feleke; Tesfahun Zemene Tafere; Ali Yimer; Wubshet Debebe Negash (BMC, 2023)
Abstract Background While progressing towards universal health coverage, poor time management in the healthcare system had significant effect on an individual such as imbalance, job dissatisfaction, and work ineffectiveness and finally poor productivity of the organization will be resulted. Information about time management practice in the healthcare system is limited. Therefore, the objective of this study was to assess time management practice and associated factors among employees working in public health centers, Dabat District, Northwest Ethiopia. Methods A facility-based cross-sectional mixed methods (quantitative and qualitative) study was conducted in Dabat District from May 27 to June 22, 2022. A simple random sampling technique was used to select 413 study subjects and for the qualitative data, six key informants were selected. Self-administered questionnaire was used for the quantitative study, and an interview guide was employed for the qualitative study. Epi-data version 4.6 and SPSS 26 software were used for data entry and analysis, respectively. Open Code 4.6 software was used for qualitative data analysis. Variables with p-value of < 0.05 in multivariable analysis were considered as significant associated factors. Results A total of 396 employees participated in the study with a response rate of 95.8%. The result showed that overall, 54.8% (95% CI: 49.5-59.6) of health employees had practiced good time management. The likelihood of good time management was higher among those health workers who had planning experience (AOR = 2.04, 95% CI: 1.22-3.4), low procrastination habit (AOR = 1.65 95% CI: 1.04-2.65), satisfied with performance appraisal (AOR: 1.7, 95% CI: 1.05-2.81), and satisfied with organizational policy and strategy (AOR: 2.6, 95% CI: 1.6-4.3). The qualitative result also showed that the existing performance appraisal practices were not linked to rewards or sanction planning. Conclusion The overall time management practice of public health center employees was low compared with prior studies. Organizational policies, prior planning experience, procrastination, and performance appraisal were all significantly associated factors with time management practice. Therefore, health center managers need to set an intervention to address all of the following factors to enhance employees' time management skills at public health centers like evidence-based performance appraisals, sharing organizational policies, and engaging in capacity building activities such as training in time management and planning.